Experimental study of riblet effects on the aerodynamic performance and flow characteristics of a delta wing. (March 2019) - Saeedi Rizi, Behnam; Nili-Ahmadabadi, Mahdi; Nafar Sefiddashti, Mehrdad; Khodabakhshian Naeini, Hamed
The present study investigates the effects of riblet on the aerodynamic performance and flow characteristics of a delta wing. Flow visualizations and measurements of the aerodynamic forces are performed on a smooth-surface as well as few textured-surface models of the delta wing. Flow visualizations were undertaken at flow speed of 2.5 m/s and various angles of attack in a vertical wind tunnel. The effects of riblet are investigated on the diameter of the vortices, location of the vortex breakdown, distance of the vortices from the wing surface, pattern of flow lines around the wing, and separation phenomenon. The results show that the riblet with a height-to-chord ratio of 0.013 has the most positive effect on the aforementioned parameters as far as drag reduction is concerned. In the second part of the study, lift and drag forces of the models are measured in a horizontal wind tunnel for a smooth-surface model as well as the other two textured models with height-to-chord ratios of 0.006 and 0.013, height-to-distance ratio of 1, sweep angle of 63.5°, and at Reynolds number of 2 × 10 5 and 0 to 35° angles of attack. The riblet-surface delta-wing model with height-to-chord ratio of 0.013 shows an increased lift-to-drag ratio at the whole range of angles of attack from 0 to 35°.